2016
DOI: 10.1093/jat/bkw070
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin, Pregabalin and Vigabatrin Quantification in Human Serum by GC–MS After Hexyl Chloroformate Derivatization

Abstract: A simple, sensitive and robust method for simultaneous determination of antiepileptic drugs (gabapentin, pregabalin and vigabatrin) in human serum using GC-MS was developed and validated for clinical toxicology purposes. This method employs an emerging class of derivatization agents - alkyl chloroformates allowing the efficient and rapid derivatization of both the amino and carboxylic groups of the tested antiepileptic drugs within seconds. The derivatization protocol was optimized using the Design of Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Before analyzing real samples, several derivatisation procedures were evaluated on standard PGB solutions. To the best of our knowledge, scant literature is available dealing with the GC–MS determination of PGB . In these contributions, chloroformate derivatives of PGB are suggested as the elective choice for the analysis of drug in pharmaceutical formulations and biological matrices.…”
Section: Resultsmentioning
confidence: 99%
“…Before analyzing real samples, several derivatisation procedures were evaluated on standard PGB solutions. To the best of our knowledge, scant literature is available dealing with the GC–MS determination of PGB . In these contributions, chloroformate derivatives of PGB are suggested as the elective choice for the analysis of drug in pharmaceutical formulations and biological matrices.…”
Section: Resultsmentioning
confidence: 99%
“…Applications of DOE in optimizing the derivatization method has been limited to GC-MS analysis. 17,18 The present study is the first application for chiral derivatization -LC-MS/MS analysis.…”
Section: Introductionmentioning
confidence: 94%
“…An initial clinical study has demonstrated the use of pregabalin as an adjuvant to labor pain relief associated with late termination of pregnancy [84]. Plasma drug concentrations can be determined via HPLC [85], LC–MS/MS [85, 86], GC–MS [87], or a fluorometric method [88]. …”
Section: Newer Antiepileptic Drugsmentioning
confidence: 99%